Managing fatigue in sarcoidosis – A systematic review of the evidence. (May 2017) - Atkins, Chris; Wilson, Andrew M
Fatigue is a common manifestation of sarcoidosis, often persisting without evidence of disease activity. First-line therapies for sarcoidosis have limited effect on fatigue. This review aimed to assess the treatment options targeting sarcoidosis-associated fatigue. Medline and Web of Science were searched in November 2015; the bibliographies of these papers, and relevant review papers, were also searched. Studies were included if they reported on the efficacy of interventions (both pharmacological and non-pharmacological) on fatigue scores in sarcoidosis patients. Eight studies were identified that fulfilled the inclusion criteria. These studies evaluated six different interventions (infliximab, adalimumab, ARA 290, methylphenidate, armodafinil and exercise programmes). There is evidence to support a treatment effect of anti-tumour necrosis factor (TNF)-αtherapies (adalimumab and infliximab) and neurostimulants (methylphenidate and armodafinil), but within five of the studies, the risk of bias was high within most domains and the remaining three studies included only small numbers of participants and were short in duration. Trial evidence for treating fatigue as a manifestation of sarcoidosis is limited and requires further investigation. Anti-TNF-α therapies may be beneficial in patients with organ-threatening disease. Neurostimulants have some trial evidence supporting improvements in fatigue but further investigation is needed before they can be recommended.